The Role of Geography in Shaping Entrepreneurship: Impacts on Venture Creation, Growth, and Sustainability - Sahil Lohan, (International Journal of Scientific Research in Science and Technology, 2024)
Geography significantly shapes entrepreneurship by influencing venture creation, growth, and sustainability. This study explores how geographic factors—such as resource availability, infrastructure, socio-cultural dynamics, and market access—determine entrepreneurial opportunities and challenges. Regions rich in resources support resource-based ventures, while resource-scarce areas often drive innovation in sustainable practices and eco-entrepreneurship. Proximity to markets and efficient logistical infrastructure further enhance connectivity, reducing costs and enabling access to larger customer bases. Socio-cultural factors, including social capital, networks, and cultural attitudes, also play a vital role in fostering entrepreneurial ecosystems, where collaboration and innovation thrive. Entrepreneurial ecosystems are often concentrated geographically in clusters and innovation hubs, facilitating knowledge spillovers, access to specialized labor, and collaborative synergies. However, regional disparities—manifested through urban-rural divides and global inequalities—create uneven entrepreneurial landscapes. Urban areas, with better infrastructure, skilled labor, and consumer markets, are more conducive to entrepreneurship, while rural and underdeveloped regions face challenges like limited resources, infrastructure deficits, and skill gaps. Addressing these disparities requires targeted interventions, such as place-based policies, infrastructure investments, and education initiatives. The study highlights the importance of fostering geographically balanced entrepreneurial ecosystems. Policies focused on enhancing transportation, digital connectivity, and vocational training are essential to reduce regional disparities and support diverse entrepreneurial ventures. By recognizing geography as a dynamic force rather than a passive backdrop, this research provides insights into creating inclusive, sustainable, and resilient ecosystems. Understanding the interplay between geography and entrepreneurship enables stakeholders to unlock regional potential and promote equitable economic growth.
Keywords: Geography; Entrepreneurship; Entrepreneurial Ecosystems, Regional Disparities; Place-Based Policies; Infrastructure Development